К ХАРАКТЕРИСТИКЕ МНОГОЛЕТНЕЙ ИЗМЕНЧИВОСТИ ЗИМНЕГО СТОКА РЕК ВОДОСБОРА ВОТКИНСКОГО ВОДОХРАНИЛИЩА (Географический вестник=Geographical bulletin, 2017)
На примере зимнего режима рек водосбора Воткинского водохранилища рассматривается возможность использования в практике гидрологических расчетов абсолютного показателя изменчивости σq наряду с относительной характеристикой Cv. Выявлены тесные зависимости между значениями σq и нормой зимнего стока, которые являются объективным критерием выделения гидрологических районов для определения коэффициентов вариации неизученных рек. Отмечено, что косвенную оценку показателей многолетней изменчивости зимнего стока малых и средних рек можно проводить без учета величины водосборной площади.To the characteristic of long-term variability of a winter runoff of the rivers of the basin Votkinskoe water storage reservoirIn the article, as an example, of the river’s runoff during the winter time, at the basin Votkinskoe water storage reservoir, the opportunity to use in practice the hydrological calculations of an absolute parameter of variability  alongside with relative characteristic Cv is considered. Close dependences between  and norm of a winter runoff which are objective criterion of allocation of hydrological regions for definition of variation coefficient for the unexplored rivers are revealed. It is shown, that the indirect estimation of parameters of a long-term variability of a winter runoff of the small and average rivers can be carried out without taking into account size of the basin area.